Autour de la table / par George Sand. - Sand, George, 1804-1876. (Tufts University. Tisch Library., 2016)
Nouvelle édition.; 1 online resource (376 pages); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.